Polyhydroxyalkanoate (PHA) purification through dilute aqueous ammonia digestion at elevated temperatures. Issue 5 (18th February 2020) - Burniol‐Figols, Anna; Skiadas, Ioannis V.; Daugaard, Anders E.; Gavala, Hariklia N.
Abstract: BACKGROUND: Purification of polyhydroxyalkanoates (PHA) is a challenging step, given the difficulty of achieving high PHA purity, while maintaining polymer integrity, in a sustainable and cost‐efficient manner. This study evaluated the potential of dilute ammonia digestion as a method to purify PHA from mixed microbial consortia. RESULTS: Digestion temperatures were critical to the obtainable purity and the amount of recovered PHA. At temperatures below 75 °C (regardless of the incubation time and ammonia concentration), a low PHA recovery (down to 65%) and no increase in purity was observed. By increasing the temperature above 75 °C, a significantly higher PHA purity and higher recovery (above 90%) could be achieved. Temperatures maximizing the purity (140 °C) led to a detrimental reduction in the molar mass of the isolated PHA, but the use of a sonication pre‐treatment enabled to increase the purity at temperatures leading to limited molar mass loss (75–115 °C). The impurities still present in the recovered PHA did not compromise its thermal stability, and no significant degradation occurred during melting of PHA with 86% purity (comparably to pure chloroform‐extracted PHA). Conversely, PHA recovered through sulphuric acid (H2 SO4 ) digestion underwent severe degradation during melting, despite presenting higher purity (98%). CONCLUSIONS: High PHA purity, recovery and thermal stability can be obtained with dilute ammonia digestion. These observations, combined with the possibility of reusing ammonia within the process, make this method a promising approach for a more sustainable purification of PHA. © 2020 Society of Chemical Industry